2015
DOI: 10.1002/ctpp.201500049
|View full text |Cite
|
Sign up to set email alerts
|

A New Scheme for High‐Intensity Laser‐Driven Electron Acceleration in a Plasma

Abstract: We propose a new approach to high-intensity laser-driven electron acceleration in a plasma. Here, we demonstrate that a plasma wave generated by a stimulated forward-scattering of an incident laser pulse can be in a longest acceleration phase with an incident laser wave. This is why the plasma wave has the maximum amplification coefficient which is determined by the breakdown (overturn) electric field in which the acceleration of injected relativistic beam electrons occurs. We estimate qualitatively the accele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…are the dimensionless group and phase velocity of the X-mode, respectively. In Equations (14) and (15), Ω h , Ω l and Ω c are the upper-hybrid, EM wave and cyclotron frequencies normalized by p . The other quantities rescaled as g = v g /c, = ( p /c) , p = ( p /c)L p , = (e/mc 2 ) and a = (e/mc )E. By solving Equation 14, Figure 3 we can obtain the evolution of the plasma wake generated by X-waves.…”
Section: Theoretical Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…are the dimensionless group and phase velocity of the X-mode, respectively. In Equations (14) and (15), Ω h , Ω l and Ω c are the upper-hybrid, EM wave and cyclotron frequencies normalized by p . The other quantities rescaled as g = v g /c, = ( p /c) , p = ( p /c)L p , = (e/mc 2 ) and a = (e/mc )E. By solving Equation 14, Figure 3 we can obtain the evolution of the plasma wake generated by X-waves.…”
Section: Theoretical Formalismmentioning
confidence: 99%
“…Wake field generation for the purpose of particle acceleration has been widely studied experimentally, analytically and using simulations. [1,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Shukla investigated analytically the generation of wake fields by circularly [22] and elliptically [23] polarized laser pulses in magnetoplasma which is found that the presence of an external magnetic field can significantly enhance the strength of plasma wake waves. The effect of magnetic field on the wake field generation by laser pulses in R and L-modes has been also investigated in Reference 24.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The advantage of using plasma for electron acceleration is the control of acceleration in these systems by using parameters such as temperature, density, magnetic field, and so forth. [1][2][3][4][5][6][7][8][9][10][11][12][13] In this way, the mechanism of electron acceleration in the interaction of electromagnetic pulses with plasmas has been taken into consideration because of its relation to many potential applications such as inertial fusion, cutting in the industry, material surface analysis, fusion, [5] fission products, and electron welding.…”
Section: Introductionmentioning
confidence: 99%